É mentira, Chico?: o humor em um tributo à imaginação popular - Ferraz, Luana (2019)
This thesis is situated in the line of research Text and discourse in the oral and written modalities and addresses the production of rhetoric by humoristic discourse. It aims to investigate the construction of laudatory discourse in the book of short stories É mentira, Terta? (1973) [Is it a lie, Terta?], by Chico Anysio. Humor is an ambivalent object capable of criticism and praise. Although humor does not have the primary objective of generating explicit debate, it always causes a reaction, whether of acceptance or repudiation. Identifying the rhetorical procedures related to laughable discourse allows us to realize how a speaker intends to promote reflections, (re)conceptualizations and (re)evaluations through the means of humor. In Chico Anysio’s (1931 – 2012) book, we find two speakers: the narrator and the main character, the humorous Pantaleão Pereira Peixoto. Our hypothesis is that there are rhetorical amplification resources in the discourses of both main speakers that give rise to the constitution of laudatory discourse regarding the character and his social group. To fulfil the intended objective, our research was founded upon the theoretical framework of Rhetoric, found especially in Aristotle (2015), Cicero (1997, 2002) and Quintilian (2015a, 2015b), and the new rhetoric, as understood from the works of Perelman and Olbrechts-Tyteca (1996), Olbrecths-Tyteca (1974) and Meyer (2007). For the analysis of the narratives, we resorted to studies by Todorov (1974) and Genette (1989), among others. With the analysis of the short stories concluded, we took notice of the amplification in the construction of the main character’s hyperbolic traits and in the production of the connecting narratives that intensify persuasion. Through amplification, the character is converted into a representation of his social group, whereas the greatness of his personality in overcoming obstacles becomes subject to praise